Clinical implications of a close vicinity of nervus dorsalis penis/clitoridis and os pubis - Sedý, Jirí; Nanka, Ondrej; Spacková, Jana; Jarolím, Ladislav (The journal of sexual medicine, 2008)
INTRODUCTION: Close relation of nervus dorsalis penis/clitoris and os pubis has a major impact in surgical disciplines. AIM: To summarize a current knowledge about this region, represented by the course of sulcus nervi dorsalis penis/clitoridis. METHODS: Literature search of years 1970-2007. MAIN OUTCOME MEASURES: In male, it accommodates nervus dorsalis penis whereas in female nervus et arteria dorsalis clitoridis. Lateral border of sulcus nervi dorsalis penis corresponds to vertical ridge and lateral border of sulcus nervi dorsalis clitoridis to ventral arc-two parameters, which are parts of the Phenice's method for sexing of isolated os pubis. RESULTS: Exact preparation of nervus dorsalis penis is crucial in correct performance of conversion of genitalia in patients with transsexualism, in reconstruction of posterior urethra, in hypospadia, during performance of penile blockade during circumcision and in revascularization surgery of erectile dysfunction. Possible role of the sulcus nervi dorsalis penis in the Alcock's syndrome is discussed. Similarly, it is advisable to take care of nervus dorsalis clitoridis during reduction clitoridoplasty in patients with adrenogenital syndrome and during the insertion of transobturator vaginal tape. Injury of nervus dorsalis penis/clitoridis leads to hypesthesia or anesthesia of glans penis/clitoridis. The injury to arteria dorsalis clitoridis leads to bleeding and/or hematoma. CONCLUSIONS: Clinical anatomy of sulci is important in several situations in urologic surgery. It is possible to use sulcus nervi dorsalis penis/clitoridis for sexing of isolated pubis for anthropological or forensic purposes.
Keywords: penis; transsexualismus; Nerve Compression Syndromes; Transsexualism; Female; Penile Diseases; Clitoris; analýza určování pohlaví; Penis; nemoci penisu; ženské pohlaví; úžinové syndromy; mužské pohlaví; Humans; lidé; Male; Sex Determination Analysis; klitoris